Socioeconomic Influences and Limited Choice of Health Care Services: A Study of the BPJS System in Indonesia - Setyawati, Niken Budi; Santiago, Faisal (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Socioeconomic inequality in Indonesia is still a major factor affecting people's access to health services, including in the BPJS Kesehatan system. Although BPJS aims to provide universal health insurance, limited collaborating health facilities, different service quality compared to the private sector, and administrative and regulatory constraints often hinder participants from getting optimal care. The impact of these limitations can be seen in the quality of services received by BPJS patients, such as long queues, delays in medical treatment, and limited medicines covered. To overcome this problem, comprehensive policy reform is needed, including increasing the number of health facilities that accept BPJS, simplifying the referral system, and increasing budget allocation to improve service quality. With these strategic steps, BPJS is expected to become a more inclusive, efficient health insurance system that can provide equitable health services for all Indonesian people.